Signalling Theory and Stock Returns: A Pre- and Post-Pandemic Comparison - Paulus, Hendro; Tarmidi, Deden (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2026)
This study examines the effect of Current ratio (CR) and Debt to Equity Ratio (DER) on stock returns, with Return on Assets (ROA) as a moderating variable, before and after the COVID-19 pandemic. It aims to explain how financial ratios are interpreted differently by investors in stable versus crisis conditions. The research uses secondary data from banking companies listed on the Indonesia Stock Exchange (IDX) during 2018–2021. A purposive sampling of 43 firms produced 172 observations, analyzed with EVIEWS 13 through comparative period testing. The novelty of this study lies in exploring the moderating role of ROA in the relationship between liquidity, leverage, and stock returns across two distinct periods, providing insights into investor behavior under uncertainty. Results show that before the pandemic, CR had a positive significant effect, DER was insignificant, and ROA strengthened the effects of both ratios on returns. After the pandemic, CR lost significance, DER showed a significant negative effect, and the moderating role of ROA shifted. These findings highlight that investor focus moved from liquidity to risk management and resilience during economic shocks. The study concludes that maintaining liquidity, prudent leverage, and sustainable profitability are vital to enhance investor confidence in crisis periods.